Dual layer vs single layer Woven EndoBridge Device in the treatment of intracranial aneurysms: a propensity score-matched analysis - Dmytriw, Adam A.; Möhlenbruch, Markus Alfred; Ulfert, Christian (Neurosurgical review, 2024)
The Woven EndoBridge (WEB) devices have been used for treating wide neck bifurcation aneurysms (WNBAs) with several generational enhancements to improve clinical outcomes. The original device dual-layer (WEB DL) was replaced by a single-layer (WEB SL) device in 2013. This study aimed to compare the effectiveness and safety of these devices in managing intracranial aneurysms.